Long-term Antibody Persistence After Hepatitis E Virus Infection and Vaccination in Dongtai, China. (28th March 2019) - Kmush, Brittany L; Yu, Huan; Huang, Shoujie; Zhang, Xuefang; Wu, Ting; Nelson, Kenrad E; Labrique, Alain B
Abstract: Background: Hepatitis E virus (HEV) is of global significance. HEV is a common cause of acute hepatitis in China. One of the major unanswered questions about HEV is the persistence of antibodies after infection and vaccination. Methods: We examined antibody persistence 6.5 years after HEV exposures through natural infection and vaccination. Ninety-seven vaccine recipients and 70 individuals asymptomatically infected with HEV enrolled in the phase III HEV239 vaccine trial in Dongtai, China, were revisited. Results: Antibody loss was 23.4% (95% confidence interval [CI], 17.1%–30.5%), with a nonsignificantly higher percentage of loss among those naturally infected (30.0%; 95% CI, 19.6%–42.1%) than those vaccinated (18.6%; 95% CI, 11.4%–27.7%; P = .085). Age and gender were not associated with antibody persistence. Only 2 people (1.2%) self-reported medically diagnosed jaundice or hepatitis-like illness in the last 10 years, both of whom had persistent antibodies. Contact with a jaundice patient and injectable contraceptive use were marginally associated with loss of detectable anti-HEV antibodies ( P = .047 and .082, respectively), whereas transfusion was marginally associated with antibody persistence ( P = .075). Conclusions: Antibody loss was more common among those naturally infected compared with those vaccinated. However, none of the characteristics examined were strongly associated with antibody loss, suggesting that factors not yet identified may play a more important role in antibody loss. Long-term postvaccination antibody persistence is currently unknown and will be an important consideration in the development of policies for the use of the highly efficacious HEV vaccine. ClinicalTrials.gov registration. NCT01014845.